2023
DOI: 10.1186/s12960-022-00784-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of workplace violence against emergency physicians in China: a cross-sectional study

Abstract: Background Workplace violence (WPV) is considered a global problem, particularly in the health sector; however, no studies have assessed the national prevalence of WPV against emergency physicians and the associated factors in China. Methods A national cross-sectional survey was conducted in 31 provinces/autonomous regions/municipalities across China between July 2019 and September 2019. A total of 15 455 emergency physicians were selected using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Therefore, the authors suggest that the authorities must introduce staff training in skills, cultural diversity, interpersonal communication, conflict management, and teamwork to prevent hospital violence in Bangladesh. It is pertinent to mention that the above recommendations have been encouraged in several studies to eliminate hospital violence or help doctors better manage in many countries [ 3 , 32 ]. Further, the Bangladesh Medical and Dental Council can integrate communication skills into medical education to ensure that future doctors develop essential knowledge on managing patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the authors suggest that the authorities must introduce staff training in skills, cultural diversity, interpersonal communication, conflict management, and teamwork to prevent hospital violence in Bangladesh. It is pertinent to mention that the above recommendations have been encouraged in several studies to eliminate hospital violence or help doctors better manage in many countries [ 3 , 32 ]. Further, the Bangladesh Medical and Dental Council can integrate communication skills into medical education to ensure that future doctors develop essential knowledge on managing patients.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a lack of empathy amongst relatives of patients for doctors. For example, when individuals are exposed to critical health conditions and wait for long times until seen by a doctor, and unmet needs or expectations such as high-level medical services even for minor, self-limiting conditions are not met; as a result, they and their relatives may experience high levels of stress, anger, and frustration, which may manifest as violence against physicians [ 32 ]. Consequently, their negative emotions are probably vented through extreme violence towards doctors as if they even resort to harming doctors violently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review reported the rates of violence from individual studies ranged from 1 incident to 172 incidents per 10,000 attendances 11 . Recently, a cross sectional study conducted in China targeting emergency physicians revealed a high workplace violence prevalence rate at 90.4% 14 …”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, a cross sectional study conducted in China targeting emergency physicians revealed a high workplace violence prevalence rate at 90.4%. 14 The under-reporting of incidents of workplace violence is not uncommon in the healthcare profession. 13,15 Workplace violence is not only limited to physical injury but also affects the mental well-being of health care workers.…”
mentioning
confidence: 99%